2020
DOI: 10.1136/bmj.m3223
|View full text |Cite
|
Sign up to set email alerts
|

Two metres or one: what is the evidence for physical distancing in covid-19?

Abstract: Physical distancing is an important part of measures to control covid-19, but exactly how far away and for how long contact is safe in different contexts is unclear. Rules that stipulate a single specific physical distance (1 or 2 metres) between individuals to reduce transmission of SARS-CoV-2, the virus causing covid-19, are based on an outdated, dichotomous notion of respiratory droplet size. This overlooks the physics of respiratory emissions, where droplets of all sizes are trapped and moved by the exhale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
305
0
27

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(341 citation statements)
references
References 36 publications
9
305
0
27
Order By: Relevance
“…Physical distancing is another important precaution to prevent the spread of COVID-19, however may be more difficult to implement in barns with narrow aisles or when assisting riding lesson students. The 2 m physical distancing rule was proposed based on studies done in the mid-19th century showing that most droplets produced by sneezing or coughing traveled less than 2 m distance, despite more recent evidence showing droplet spread up to 8 m away [7]. Most riding facilities approached physical distancing by limiting the number of people on the property or limiting access to certain areas of the facility to reduce the opportunities for close contact to other people.…”
Section: Discussionmentioning
confidence: 99%
“…Physical distancing is another important precaution to prevent the spread of COVID-19, however may be more difficult to implement in barns with narrow aisles or when assisting riding lesson students. The 2 m physical distancing rule was proposed based on studies done in the mid-19th century showing that most droplets produced by sneezing or coughing traveled less than 2 m distance, despite more recent evidence showing droplet spread up to 8 m away [7]. Most riding facilities approached physical distancing by limiting the number of people on the property or limiting access to certain areas of the facility to reduce the opportunities for close contact to other people.…”
Section: Discussionmentioning
confidence: 99%
“…Second, studies of health-related behaviours usually focus on one type of behaviour (e.g., smoking or drinking) or a range of closely related behaviours (e.g., eating habits). COVID-19 related recommendations cover more diverse types of behaviours not necessarily closely related, such as keeping physical distance and washing hands frequently (Alwan et al, 2020;Chu et al, 2020;Ioannidis, 2020;Jones et al, 2020;Rundle et al, 2020). Third, while previously studied behaviours have direct personal benefits, this is not the case for COVID-19 recommendations.…”
Section: Explaining Different Types Of Health Behavioursmentioning
confidence: 99%
“…Their elements are occupancy of rooms, meeting time, activity (breathing, speaking, and shouting), and wearing of face coverings. The authors clearly demonstrated that the risk of infection increases with occupancy and presence of SARS-CoV-2 in most situations reviewed [29].…”
Section: Discussionmentioning
confidence: 94%